Phototherapy with turquoise versus blue light. Issue 5 (1st September 2003) - Ebbesen, F; Agati, G; Pratesi, R
Abstract : Preterm jaundiced infants were treated by phototherapy with a new turquoise fluorescent lamp. This was more effective in reducing plasma total bilirubin in relation to light irradiance than the ubiquitously used blue fluorescent lamp.